2012
DOI: 10.1186/1471-2458-12-988
|View full text |Cite
|
Sign up to set email alerts
|

Measuring financial protection for health in families with chronic conditions in Rural China

Abstract: BackgroundAs the world’s largest developing country, China has entered into the epidemiological phase characterized by high life expectancy and high morbidity and mortality from chronic diseases. Cardiovascular diseases, chronic obstructive pulmonary diseases, and malignant tumors have become the leading causes of death since the 1990s. Constant payments for maintaining the health status of a family member who has chronic diseases could exhaust household resources, undermining fiscal support for other necessit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
39
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 27 publications
11
39
3
Order By: Relevance
“…These findings, which rely on direct costs for CNCDs aggregated at the household level, support findings from our previous work, which pointed at the regressivity of individual out-of-pocket expenditure on CNCDs [45]. These findings are also consistent with prior analyses of catastrophic spending, which included chronic conditions as an explanatory variable in models targeting the overall economic burden due to ill health in SSA [14, 15] and in LMICs more in general [28, 39, 42, 50, 51]. These studies had already indicated how suffering from a chronic condition represented an important determinant of catastrophic spending.…”
Section: Discussionsupporting
confidence: 89%
“…These findings, which rely on direct costs for CNCDs aggregated at the household level, support findings from our previous work, which pointed at the regressivity of individual out-of-pocket expenditure on CNCDs [45]. These findings are also consistent with prior analyses of catastrophic spending, which included chronic conditions as an explanatory variable in models targeting the overall economic burden due to ill health in SSA [14, 15] and in LMICs more in general [28, 39, 42, 50, 51]. These studies had already indicated how suffering from a chronic condition represented an important determinant of catastrophic spending.…”
Section: Discussionsupporting
confidence: 89%
“…Health-related factors affecting CHE in our study included self-rated health and chronic those, similar to the results of previous studies on persons with no disability [24, 25] and persons with a disability and chronic diseases [2628]. If a household includes a person with chronic diseases, they would be likely to continually incur medical expenses that may be increased by expenses not covered by health insurance.…”
Section: Discussionsupporting
confidence: 64%
“…NCMS plus NEMS was a protective factor of CHE and impoverishment. Similar to households with hospitalised members, households with income below the poverty line had significantly higher odds of CHE, and having household members aged over 60 was significant risk factor of incurring impoverishment, as demonstrated in prior studies .…”
Section: Discussionsupporting
confidence: 63%
“…Nowadays, health finance reform is implemented in many countries to minimise OOP payments, especially for poor people or those with chronic diseases [8,9]. Due to limited financial budgets, most health insurances provide protection against healthcare expenditures of inpatient services only [9,10]. However, those who have chronic diseases need frequent outpatient services and medication; thus, well-planned health financial reform is important [9,11,12].…”
Section: Introductionmentioning
confidence: 99%